“Atende aí que é a readaptada da tarde!” sentidos-e-significados do trabalho do professor em readaptação - Oliveira, Rosemeyre Moraes de (2018)
This PhD thesis, situated in the field of Applied Linguistics, aims to contribute to research in an educational context through the ILCAE Group - Linguistic Inclusion in Scenarios of Educational Activities (PUC-SP), to contribute qualitatively with the impressions provided by the participating school managers, faculty teachers and teachers undergoing readaptation for future actions focused on public policies and local actions in schools regarding the reallocation and recovery of these professionals and, as specific objectives, to critically understand the senses-andmeanings of the teacher's work as described by the referred participants. This study is a qualitative research with a critical interpretation base (Triviños, 2008) based on a social-historical-cultural theoretical framework and on studies on affectivity carried out by Vygotsky (1934/1984, 1989 and 2001) and the social exclusion-inclusion dialectic addressed by Sawaia (2012), through the ergological studies of Schwartz (1996, 1998, 2000, 2002, 2003, 2004, 2006). Like other studies that investigate teacher work and the discourses derived from teaching activities within this work, this research brings a certain novelty in presenting speeches related to the functional readaptation of a teacher gathered and analyzed by a readapted researcher teacher, the readapted of the afternoon referred to in the title. The elected epistemic axis fosters social transformation through language. The central question that guides this research is tripartite by the categories of the involved actors and, through their answers, we attempted to understand "(i) by the members of the School Management? (ii) by the faculty members in office? (iii) by the faculty members undergoing functional readjustment? The analyzed corpus is composed of answers obtained through semi-structured interviews with the indicated actors, carried out in schools that were seconded to Teaching Offices 3 and 4 of East Teaching, Center- South, South 2 and Campinas during 2015, 2016 and the first semester of 2017. After analyzing the lexical choices used by the participants, the recurrence of similar terms indicates that: the teacher undergoing readaptation is, in most cases, seen as a non-teacher; many participants pointed out the current public policies regarding the teacher undergoing readaptation as responsible for the lack of preparation for the return to classes and for the disregard of which theme is treated by those directly involved in the teacher's work routine. The main complaint is social exclusion is, followed by lack of medical services that support the teacher undergoing readaptation, while the third complaint demonstrates that relocation in spaces in direct contact with students and with extreme noise aggravates anxiety and panic scenarios, and that work in the office and in the school corridors is the greatest factor for the professional and personal disqualification of the readapted, erasing their identification as a "teacher"